The Role Of Parents In Motivating Student Learning Activities In Remote Areas - Susanto Susanto (Concept: Journal of Social Humanities and Education, 2024)
Introduction: Parents are so busy earning a living that they sometimes forget about their children's learning activities at home. Objective: This study aims to determine the role of parents in increasing students' learning motivation in primary schools in remote areas. Methods: This study used a qualitative approach. Qualitative research is conducted directly over time and directly within the scope of the environment, data analysis uses an inductive approach especially during initial research. Researchers use descriptive research to describe things related to real conditions in the field. The tools used in this research are questionnaires, interview guidelines, and documentation. After the data was collected, it was analyzed using descriptive analysis. Results: This study shows that parents play a role in generating student learning motivation. This was conveyed by children who stated "they are very happy if accompanied by parents when studying at home". Conclusion: Providing motivation is important for parents so that children can learn well at home and at school, because parents are children's motivators in generating children's learning motivation before children are guided by teachers at school.